Blackpink's Celebrity Endorsement Shapes Global Oreo Purchase Intentions: Dukungan Selebriti Blackpink Membentuk Niat Pembelian Oreo Global - Ina Fitria; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2024)
This research investigates how Celebrity Endorsement and Brand Image influence Purchase Intention for Oreo Blackpink products, with Brand Attitude as a mediator, aiming to fill a gap in understanding consumer behavior in the context of South Korean music group endorsements. Using quantitative techniques and data from 177 respondents who had seen advertisements and purchased Oreo Blackpink products, the study found that Celebrity Endorsement and Brand Image positively and significantly influence Brand Attitude. However, Brand Image did not significantly affect Purchase Intention, while Celebrity Endorsement and Brand Attitude had a positive and significant impact on Purchase Intention. The findings emphasize the importance of celebrity endorsement selection and Brand Attitude in shaping consumer perceptions and purchase intentions, providing insights for marketing strategies in competitive markets targeting emerging demographics. Highlight: Celeb Influence: Key in shaping perception and purchase for Oreo Blackpink. Attitude's Role: Crucial mediator between endorsement, image, and purchase intention. Strategic Insight: Selective endorsement and positive attitude enhance consumer engagement. Keyword: Celebrity Endorsement, Brand Image, Purchase Intention, Brand Attitude, Oreo Blackpink